Inkonsistensi Pengaturan Kewenangan Pembuatan Risalah Lelang oleh Notaris - Fatria Hikmatiar Al Qindy (Fakultas Hukum Universitas Airlangga, 2021)
Notary is a general official authorized to make authentic deed, one of which is making the deed of auction document in accordance with the Notary Position Act, but in other provisions, the Auction Regulation states that the authorized to make the deed of auction is the Auction Officer which raises the issue of who is authorized to make the deed of the auction minutes. This study aims to find out the legal consequences if the notary makes the minutes of auction document and the authority of the notary in making the deed of the auction according to Law Number 2 of 2014 concerning Amendments to the Notary Position Act. This research is a normative research, the approach used is the legislation approach and conceptual approach. Based on the results of this study that the authorized to make the auction minutes is the Auction Officer not a Notary but the Notary can make the auction minutes if the notary concurrently serves as an Auction Officer, namely as Class II Auction Officer. Notary makes the deed of auction document in his capacity as an Auction Officer not as a Notary, then the legal consequence if the Notary makes the deed of auction document is the deed is null and void, the cancellation is done through the court and if any party is harmed by the deed, the Notary can be sued for an act against the law which is a compensation claim.Keywords: Notary; Minutes of Auction; Auction Officer.Notaris adalah pejabat umum yang berwenang untuk membuat akta autentik salah satunya adalah membuat akta risalah lelang sesuai dengan Undang-Undang Jabatan Notaris, namun dalam ketentuan lain yakni Peraturan Lelang menyebutkan bahwa yang berwenang membuat akta risalah lelang adalah Pejabat Lelang sehingga menimbulkan masalah siapakah yang berwenang untuk membuat akta risalah lelang. Penelitian ini bertujuan untuk mengetahui akibat hukum apabila notaris membuat akta risalah lelang dan kewenangan notaris dalam membuat akta risalah lelang menurut Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan Undang-Undang Jabatan Notaris. Penelitian ini adalah penelitian normatif, pendekatan yang digunakan adalah pendekatan perundang-undangan dan pendekatan konseptual. Berdasarkan hasil penelitian ini bahwa yang berwenang membuat risalah lelang adalah Pejabat Lelang bukan Notaris namun Notaris dapat membuat risalah lelang apabila notaris merangkap jabatan sebagai Pejabat Lelang yakni sebagai Pejabat Lelang Kelas II. Notaris membuat akta risalah lelang dalam kapasitasnya sebagai Pejabat Lelang bukan sebagai Notaris, kemudian akibat hukum apabila Notaris membuat akta risalah lelang adalah akta tersebut batal demi hukum yang pembatalannya dilakukan memalui pengadilan dan bila ada pihak yang dirugikan atas dibuatnya akta tersebut maka Notaris dapat digugat melakukan perbuatan melawan hukum yang merupakan gugatan ganti rugi.Kata Kunci: Notaris; Risalah Lelang; Pejabat Lelang.